Research in the General of the Special Type System in Three-Dimentional Space - B, Khusanov; M, Turaev (European Journal of Life Safety and Stability (2660-9630), 2022)
In the work was studied a qualitative picture of the trajectories of a three-dimensional system of a special type and obtained that if the algebraic equation has not real solutions, then for e(ad-bc)≠0 this system can have five, three or one exceptional direction adjacent to the origin.